TRAINING ON FINANCIAL STATEMENT MANAGEMENT USING MICROSOFT EXCEL TO CITIZENS TANJUNG DUREN, WEST JAKARTA - Agtovia Frimayasa; Ibnu Haris Nasution (Journal of Community Service and Engagement, 2022)
With the development of increasingly advanced technology today, it is undeniable that information technology and computers are one of the most basic human needs, the use of computers today can be done routinely for important tasks involving large amounts of data in a company, help every job in the field of computerization in the world of industry, education, sports, health and so on (Maimunah et al., 2017)Some MSMEs have used computer processes for financial management, such as filing, calculating, and making reports, so it doesn't take a long time. So far, MSMEs in using computers is only limited to typing activities. Therefore, it is necessary to develop the potential for MSME actors, for example in providing financial reports. Microsoft Excel training for residents of Tanjung Duren Utara can provide new benefits for participating actors in filing, calculating, and managing financial reports. Automatic calculations can increase the effectiveness of the performance of MSME actors in making financial report recaps.The existence of this community service is to provide management training using Microsoft Excel. So we hope that with this training, it will be a start to find out and make a profit and loss report quickly on the business being run so that it can increase business turnover. This training activity, it is held Virtually through the Zoom Meeting Application. With this socialization, it is hoped that MSME actors can make reports quickly and validly so that they can increase their business turnover.